2013
DOI: 10.1155/2013/297501
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic and Functional Profiling of Crohn's Disease: Autophagy Mechanism and Susceptibility to Infectious Diseases

Abstract: Crohn's disease is a complex disease in which genome, microbiome, and environment interact to produce the immunological background of the disease. Disease in childhood is more extensive and characterized by a rapid progression, leading to severe repercussions in the course of the disorder. Several genetic variations have been associated with an increased risk of developing the disease and most of these are also implicated in other autoimmune disorders. The gut has many tiers of defense against incursion by lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…In mucous membrane function, the disorders of autophagy affect some aspects of innate and acquired inflammatory response, e.g. function of Paneth cells, cytokines production, pathogens clearance and, what was showed in last time, decrease function of goblet cells and absorptive function of microvilli [18,19].…”
Section: Activity Of Immunocompetent Cells and Overproduction Of Cytomentioning
confidence: 99%
See 3 more Smart Citations
“…In mucous membrane function, the disorders of autophagy affect some aspects of innate and acquired inflammatory response, e.g. function of Paneth cells, cytokines production, pathogens clearance and, what was showed in last time, decrease function of goblet cells and absorptive function of microvilli [18,19].…”
Section: Activity Of Immunocompetent Cells and Overproduction Of Cytomentioning
confidence: 99%
“…Like in other chronic inflammatory diseases, the inducing factor is unknown, but it is believed, that interaction between genetic background and environmental factors, mainly intestinal microbiota, leads to the disease. In last 20 years two tendencies are noted: increased number of patients and decrease in age, so children before age of 2 years fulfilling the criteria of CD are observed [19,25,31,53]. The clinical symptoms are very heterogeneous, due to localization of inflammation in any part of gastrointestinal tract from mouth to anus, age of patient, time of process before onset [19].…”
Section: Crohn's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Crohn's disease (CD) is a chronic form of inflammatory bowel disease (IBD) that can affect any part of the gastrointestinal tract, ranging from the mouth to the anus 1 . Studies have shown that interleukin 10–deficient (IL‐10 −/− ) mice display similar characteristics to those of human patients with CD 2 .…”
Section: Introductionmentioning
confidence: 99%